Environmental challenges and perspectives of the fresh-cuts sector in Italy - Galioto, Francesco; Zucaro, Raffaella; Pergamo, Raffaella (Frontiers in Sustainable Food Systems, 2022)
This perspective paper provides insights on the characteristics of the fresh-cut sector in Italy and on the key environmental challenges the sector is currently facing. Specifically, the paper investigates the factors that brought to the development of agro-industrial hubs for fresh-cuts, capable of influencing the income and employment of various local communities in Italy and the factors that contributed causing serious environmental issues, especially related to the disposal of packaging waste and to the consumption and pollution of water resources. Such issues were recently addressed by the EU through dedicated directives and regulations. These regulations require a serious reflection on the strategies to be undertaken for the future of the sector and the surrounding socioeconomic context. The paper concludes with some policy recommendation to overcome existing barriers and, eventually, transform them into opportunities.